Analisis Financiero A La Empresa “Espinosa Aguirre Cia. Ltda.” En Los Años 2011 - 2012 - Aguilar Cueva, Greta Paulina (2014)
The subject of this thesis was developed with the aim of: performing a "FINANCIAL ANALYSIS COMPANY A ESPINOSA AGUIRRE CIA. LTDA. IN THE YEARS 2011-2012 ", in order to know the current financial position of the same by applying indicators to verify the working capital, liquidity, leverage, activity and profitability. Its development allowed fulfill the objectives among which stand out: Determination of capital, labor, liquidity, leverage and activity applied to the needs of the company with which we show that the same is fit to operate efficiently and effectively as it has been doing. They met and analyzed the trends of different financial variables, which explained graphically different and concrete results. A report will be prepared based on the results obtained in order to contribute to a correct decision by their management improvement tips and finally raised to meet the goals set according to the report presented. Once completed the financial analysis, it was found that the company has not made any financial analysis from date of creation that has not been able to establish results of financial ratios that can contribute to better decision making by what is recommended their managers ask the finance department to perform these indices in the end of each year after establishing the differences with the previous year. Presented the report obtained